Analisis Data Hotspot di Kawasan Strategis Provinsi (KSP) Rawa Batang Banyu Provinsi Kalimantan Selatan Tahun 2009–2018 - Agda Primaraniyanti; Ichsan Ridwan; Sudarningsih Sudarningsih (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2022)
ABSTRACT− Forest and land fires are a very serious issue in Indonesia, especially in KSP Rawa Batang Banyu which has the potential to experience sustainable development. Hotspots created by NASA-FIRMS (National Aeronautics and Space Administration - Fire Information for Resource Management System) can indicate forest and land fires. The purpose of this study is to analyze the number and density of hotspots with the correlation between hotspots and rainfall with ONI and rainfall in the last 10 years (2009-2018). This study uses Spatial analysis, Time Series Analysis, Pearson Correlation analysis, with hotspot, rainfall, and ONI data that have been released. As a result, the hotspot density conditions in each region were concentrated in Cintapuri Darussalam, Banjar Regency and Binuang, Tapin Regency. Real-Time Analysis shows the highest number of hotspots in the 2009-2018 period reached its highest point in September. Pearson correlation analysis between hotspot and rainfall data shows a value of -0.224 which indicates that the relationship is very weak and inversely proportional. The correlation between ONI data and rainfall shows a value of -0.066 which indicates that the relationship is weaker than the previous correlation and also inversely proportional.